2006
DOI: 10.1097/00007691-200608000-00010
|View full text |Cite
|
Sign up to set email alerts
|

??9-Tetrahydrocannabinol, 11-Hydroxy-??9-Tetrahydrocannabinol and 11-Nor-9-Carboxy-??9-Tetrahydrocannabinol in Human Plasma After Controlled Oral Administration of Cannabinoids

Abstract: A clinical study to investigate the pharmacokinetics and pharmacodynamics of oral tetrahydrocannabinol was performed. This randomized, double-blind, placebo-controlled, within-subject, inpatient study compared the effects of THC-containing hemp oils in liquid and capsule form to dronabinol (synthetic THC) in doses used for appetite stimulation. The National Institute on Drug Abuse Institutional Review Board approved the protocol and each participant provided informed consent. Detection times and concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…An explanation for the negative sweat patches may be that there is less THC in blood available to distribute into sweat following oral ingestion compared to smoking, due to degradation in the stomach and first pass metabolism via the oral route. For subjects in the present study, Goodwin et al reported plasma THC concentrations less than 6.1 μg/L [21]. Subjects smoking a cigarette containing 15.8 mg THC had mean maximum plasma THC concentrations of 84.3 μg/L [23].…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…An explanation for the negative sweat patches may be that there is less THC in blood available to distribute into sweat following oral ingestion compared to smoking, due to degradation in the stomach and first pass metabolism via the oral route. For subjects in the present study, Goodwin et al reported plasma THC concentrations less than 6.1 μg/L [21]. Subjects smoking a cigarette containing 15.8 mg THC had mean maximum plasma THC concentrations of 84.3 μg/L [23].…”
Section: Discussionmentioning
confidence: 41%
“…Various oral doses were administered three times daily for five consecutive days during the study period and included doses up to 14.8 mg THC daily for the five-day regimens. For the same subjects, Goodwin et al reported that all plasma THC concentrations were less than 6.1 μg/L [21]. Measured plasma THC concentrations during this oral administration study were much lower than THC concentrations observed during cannabis smoking [23].…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…These effects remained statistically significant for relative theta power but were less evident and not statistically significant for relative sigma power when considering the full 8-hour PSG recording period. This temporal pattern could be expected based on the pharmacokinetics of the drug, as the first-compartment plasma elimination half-life of oral dronabinol is 2 to 3 hours, 15,16 and with daily dosing, plasma concentrations return to or near to baseline levels within 4 to 5 hours of drug administration.…”
Section: Discussionmentioning
confidence: 94%